Augmented Reality sebagai Media Edukasi Sejarah Bangunan Peninggalan Kesultanan Utsmaniyah menggunakan Metode Marker Based Tracking dan Algoritma Fast Corner Detection - Muhammad Fayiz; Naufal Hilmy; Ucuk Darusalam; Albaar Rubhasy (KITA Institute, 2020)
At this time, information and communication technology is growing rapidly. One example of technological developments is Augmented Reality (AR). Augmented Reality in theory is to present virtual effects in the real world. This AR technology has been applied in several fields. One of them is in the field of education. In this study, an AR application was made as an educational medium for the history of the heritage buildings of the Ottoman Empire, especially for Madrasah students in the subject of Islamic Cultural History (SKI). This research will discuss the history of heritage buildings of the Ottoman Empire such as; Hagia Sophia Monument, Yeni Valide Mosque, and Blue Mosque. The Ottoman Empire was one of the world's Islamic empires that played a major role in the spread of Islamic teachings. This AR application uses the Marker Based Tracking method and the Fast Corner Detection algorithm. The tools used are Android Studio, Unity 3D, Sketchup, Figma, and Vuforia. The results of this study resulted in the application having succeeded in displaying a 3D Object from the Ottoman Sultanate heritage building, along with a description next to the 3D Object. In addition, this Monument AR application also works well on the Android operating system.